Change in performance in response to training load adjustment based on autonomic activity - Botek, M.; McKune, A. J.; Krejci, J.; Stejskal, P.; Gaba, A. (International Journal of Sports Medicine, 2014)
The primary aim of this study was to assess performance (Perf) changes in response to a new training strategy. Specifically, based on spectral analysis of heart rate variability (SA HRV) to determine autonomic nervous system (ANS) activity, training doses were adjusted to maintain vagal activity at a high and relatively stable level during training preparation. Trained athletes (5 male and 5 female) aged 23.2±4.2 years voluntarily participated in the study. ANS activity was assessed during an orthoclinostatic test, and was represented by calculating HRV variables and a total score index. Over 17 weeks, improvement (1.4-8.5%) and deterioration (0.1-8.8%) in Perf were detected in 7 and 3 athletes, respectively. A relationship (rs=0.684; P<0.05) between the change in Perf (Delta Perf) and supine PHF during season was found. Supine HRV indices (PHF, PT, and MSSD) for the last 3 weeks of the HRV-adjusting period correlated (rs=0.636; 0.648; 0.648, P<0.05) with Delta Perf. Based on the results, a high and relative stable vagal activity during preparation may indicate a readiness to train or appropriate recovery that positively affects Perf. In conclusion, daily quantification of ANS activity by SA HRV seems to be a promising tool for the enhancement of Perf.